Building Resilience Through Strengths-Based Learning During Graduate Study Abroad: An Exploratory Study. (September 2019) - Dresen, Chelsea K.; Wilmes, Matthew L.; Sullivan, Karen R.; Waterbury, Theresa A.
Background: Leadership growth during short-term study abroad programs remain of critical interest to educators. No research exists on how a strengths-based study abroad curriculum influences resilience growth for working adult graduate students.Purpose: This exploratory study sought to examine how utilizing a strengths-based curriculum contributes to the development of resilience in graduate students during a study abroad program.Methodology/Approach: An online, open-ended survey was distributed to 11 students who participated in a 2018 graduate study abroad program to New Zealand. Responses were analyzed to identify themes by faculty-organized and student-organized activities.Findings/Conclusions: A strengths-based curriculum contributed to the perceived growth of resilience during a study abroad program by providing opportunities to manage, adjust, and overcome challenges. All 11 respondents perceived growth in resilience when planning and implementing the student-organized activities, whereas 9 of the 11 students reported resilience growth within the faculty-organized activities.Implications: Graduate study abroad programs provide a rich environment in which to experience growth in resilience through peer engagement and reflection. The strengths-based curriculum establishes a common language in which to discuss challenges and reflect on experiences.